Principal Raudhatul Athfal's Participatory Behavior Practices in Implementing the Independent Curriculum in Indonesia - Novan Ardy Wiyani; Novi Mulyani; Wan Alawee Samaeng (Jurusan Manajemen Pendidikan Islam Fakultas Tarbiyah dan Keguruan UIN Sultan Maulana Hasanuddin Banten, 2023)
This research aims to describe and analyze the participatory behavioral practices of head Raudhatul Athfal in implementing the independent curriculum. This research uses a qualitative approach with a phenomenological type of research. Data was collected using interview, observation and documentation techniques. The data that has been collected is then analyzed using the Miles and Huberman model data analysis technique, which consists of data reduction, data display and verification. The research results show that the practice of participatory behavior towards teachers in implementing the independent curriculum and religious moderation at Raudhatul Athfal (RA) Nurul Dzikri is carried out through the following three efforts: (1) Involving teachers in making decisions related to the implementation of the independent curriculum; (2) Involving teachers in exercising self-control over their performance in implementing the independent curriculum and giving autonomy to teachers to work to complete their tasks and (3) Involving teachers in controlling leadership practices in implementing the independent curriculum. These three teacher involvements have positioned teachers as designers and primary implementers in implementing the independent curriculum. It gives them broad autonomy to manage the independent curriculum in the classroom. The involvement of teachers in making decisions related to the implementation of the independent curriculum, the involvement of teachers in controlling themselves and controlling the leadership of the school principal in implementing the independent curriculum, as well as their full authority to work following their ideas and creations make teacher performance in implementing the independent curriculum focused, organized and well managed by the school principal.